PTEN hamartoma-tumour syndrome: a model for the practice of clinical cancer genetics - Eng, Charis (Henry Stewart Talks, 2014)
PTEN Hamaratoma Tumour Syndrome: A Model for the Practice of Clinical Cancer Genetics, Clinical cancer genetics, Evaluating and managing families with inherited cancer syndromes, Recognition of clinical signs of heritable cancer, PTEN hamartoma tumor syndrome as paradigm, Recognition, Gene-specific medical management